Quality of life of patients subjected to specific allergen immunotherapy - Kubik, Barbara; Romanowska, Urszula; Bednarz, Elżbieta (Health Promotion & Physical Activity, 2017)
Introduction: At present, allergic diseases are some of the most common chronic diseases affecting all spheres of human life. The only form of causative treatment of allergic diseases, apart from elimination of the sensitizing factor, is the specific allergen immunotherapy. The symptoms of allergic diseases can cause a number of consequences, including reduction of patient activity, negatively affect social relationships, ways of spending free time, and also cause sleep disorders. Assessing the quality of life in allergic diseases provides us with knowledge of the patient’s psychological and social functioning, and is a valuable addition to the review of the effectiveness of treatment for allergic diseases, allowing us to assess the patient’s overall well-being. Aim of the study: The aim of the study was to evaluate the quality of life of patients using specific allergen immunotherapy. Material and methods: 128 subjects were included in the study, but 100 questionnaires were used for the analysis. The study group was comprised of patients undergoing specific allergen immunotherapy over the age of 18 years. In this paper a diagnostic survey was used as a research method. The tools used are the standard questionnaire SF-36 and the questionnaire survey. Results: In the present study, it was observed that the overall quality of life of people affected by allergic diseases, as measured by the SF-36 questionnaire, can be assessed as quite good. Respondents subjected to specific allergen immunotherapy consider this method of treatment positively influencing their health as they reduce the symptoms of allergies. As many as 91% of the respondents think that specific immunotherapy affects them to reduce the symptoms of allergies. It has also been shown that the length of therapy has no effect on reducing the symptoms of allergies. Conclusions: The overall quality of life of patients is quite good, best evaluated in the domains of physical fitness, limitation of activity caused by emotional problems and changes in health status. Researchers positively evaluate the effect of immunotherapy on their health as it reduces the symptoms of allergies. Respondents have little knowledge about how to prevent exposure to allergens. Despite a positive assessment of the effectiveness of immunotherapy, the vast majority of respondents feel the need for additional antihistamines.